2005
DOI: 10.4049/jimmunol.174.4.1906
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal γδ T Cells Develop in Mice Lacking Thymus, All Lymph Nodes, Peyer’s Patches, and Isolated Lymphoid Follicles

Abstract: Through analysis of athymic (nu/nu) mice carrying a transgenic gene encoding GFP instead of RAG-2 product, it has recently been reported that, in the absence of thymopoiesis, mesenteric lymph nodes and Peyer’s patches (PP) but not gut cryptopatches are pivotal birthplace of mature T cells such as the thymus-independent intestinal intraepithelial T cells (IEL). To explore and evaluate this important issue, we generated nu/nu mice lacking all lymph nodes (LN) and PP by administration of lymphotoxin-β receptor-Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 52 publications
2
46
0
Order By: Relevance
“…Taken together, these data indicate that IL-15 establishes permissive V γ 5 gene segment accessibility for directed gene rearrangement in both the thymus and intestine. Whether sufficient functional recombinase activity exists in the putative intestinal lymphoid precursors of normal mice is controversial 39,40 , but irrespective of anatomical sites, our results show that IL-15 programs targeted enhancement in V γ 5 gene accessibility conducive for selective gene rearrangement.…”
Section: Il-15 Control Of Vγ5 Gene In Intestinal Lymphoid Cellmentioning
confidence: 68%
See 2 more Smart Citations
“…Taken together, these data indicate that IL-15 establishes permissive V γ 5 gene segment accessibility for directed gene rearrangement in both the thymus and intestine. Whether sufficient functional recombinase activity exists in the putative intestinal lymphoid precursors of normal mice is controversial 39,40 , but irrespective of anatomical sites, our results show that IL-15 programs targeted enhancement in V γ 5 gene accessibility conducive for selective gene rearrangement.…”
Section: Il-15 Control Of Vγ5 Gene In Intestinal Lymphoid Cellmentioning
confidence: 68%
“…Recent findings have indicated the exclusive origin αβTCR + i-IELs from CD4 + CD8 + thymocytes in euthymic mice 4 , but the situation remains murky for γδ i-IELs. The developmental requirements for γδ i-IELs are distinct from those of αβ i-IELs 4,10 and suggestive evidence for the extrathymic development of γδ i-IELs exists 40,45 . However, in unperturbed normal mice, robust RAG1 and RAG2 expression is difficult to detect in the gut 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These thymus-independent T cells develop mainly in the intestine and liver and include certain subsets of TCR␣␤ ϩ and ␥␦ ϩ T cells (22). It has previously been shown that the numbers of thymus-independent T cells increase in parallel with thymic involution (23,24).…”
Section: Characterization Of Peripheral T Cell Subsetsmentioning
confidence: 99%
“…Although the majority of classical intestinal T cells arise in the thymus (15) and home to the gut, there is evidence that specialized T cell subsets develop locally in the intestine (14,16). If lymphoid development occurs in the intestine, precursors and factors required for their maturation should be present (14).…”
mentioning
confidence: 99%